Mobile app for tours & travels with AR/VR - Wei, Haoran (Nanyang Technological University, 2022)
Rising technology has created new chances for tourism in Singapore under the pandemic. This paper will showcase HiSG, a new travel smartphone app that blends augmented reality technology and virtual reality photography to improve users’ experience and increase their passion for traveling in Singapore. The app is built with the Flutter user interface framework, and the Wikitude SDK offers geographical information based augmented reality functionalities. Google Cloud Platform hosts the backend authentication, database, and storage services. The Google Maps Platform and the Tourism Information & Service Hub application programming interfaces are used to support some of the data and functionality in this project. This report discusses the project’s objectives, literature review, and the design and implementation of the technology stack and the application functionalities. Finally, an analysis of the learning outcomes and project management is presented.